GAMIFICATION-BASED ASSISTED LEARNING VIDEO DEVELOPMENT IN BASIC STATISTICS FOR DEAF STUDENTS - Nisak Ruwah Ibnatur Husnul; Vivi Iswanti Nursyirwan (Universitas Negeri Makassar, 2022)
This study aims to produce gamification-based video assisted learning in basic statistics for deaf students whose validity and reliability have been tested. This research is a development research using the ADDIE model. The subjects in this study were 2 statistical material experts, 2 learning video media experts, 2 practitioners and 15 student responses. The data collection method used an instrument in the form of a rating scale with a gamification-based video-assisted learning validity assessment sheet. The data analysis technique used is the ADDIE method in development research. The data were analyzed using the mean formula to obtain the average score. The average score of material experts is 4.7, media expert is 4.6, practitioner response is 4.66, and response is great 4.72 students with an overall qualification of